Hermite-Hadamard and Simpson Type Inequalities for Differentiable P-GA-Functions. (22nd May 2014) - İşcan, İmdat
Abstract : The author introduces the concept of theP -GA-functions, gives Hermite-Hadamard's inequalities forP -GA-functions, and defines a new identity. By using this identity, the author obtains new estimates on generalization of Hadamard and Simpson type inequalities forP -GA-functions. Some applications to special means of real numbers are also given.